Evaluation of light and pheromone combined traps for mass capture of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in greenhouse tomato production - Castresana, Jorge Eduardo (2026)
Arthropod pests pose a significant threat to horticultural crops globally, with the tomato leafminer, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) is a particularly damaging pest for greenhouse tomato cultivation. The larvae of tomato leafminer cause direct damage by creating galleries in leaves, shoots, and immature fruits. Its feeding negatively affects photosynthesis and reduces the aesthetic quality of the fruit, leading to substantial economic losses. The study aimed to evaluate the effectiveness of various homemade traps using light-emitting diodes (LEDs) powered by solar energy in combination with pheromones for capturing adult tomato moths as an ecological alternative for control in a protected tomato crop in Concordia, Argentina. Several trap types were tested, including LEDs at 390 nm and 470 nm, either alone or in combination with sex pheromones. Additionally, these traps were compared to a standard sex-pheromone trap included in this experiment. The study used a completely randomized block design with two replications in greenhouses, with traps randomly distributed at equidistant intervals in the aisles and rotated every two weeks to prevent capture bias. The study was carried out over two consecutive years with weekly monitoring. The weekly mean number of male tomato leafminers was evaluated. Results indicated that the trap using 470 nm LEDs in combination with sex pheromones recorded a higher number of tomato leafminer captures than the remaining traps.